2013
DOI: 10.1074/jbc.m112.398073
|View full text |Cite
|
Sign up to set email alerts
|

The Human Tim-Tipin Complex Interacts Directly with DNA Polymerase ϵ and Stimulates Its Synthetic Activity

Abstract: Background:The Tim-Tipin complex plays a critical role in the S phase checkpoint and replication fork stability by a molecular mechanism not yet elucidated. Results: The human Tim-Tipin complex specifically enhances the synthetic activity of DNA polymerase ⑀. Conclusion: The Tim-Tipin complex could modulate the DNA polymerase ⑀ function at the replication fork. Significance: These findings further our understanding of the replication fork dynamics in metazoans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…Replisome components are usually stably associated to replication forks 27 . Tipin is required for efficient Pol α binding to chromatin, and it has been shown to increase processivity of all major DNA polymerases 3 , 8 . It is possible that the Tipin facilitates polymerase-mediated DNA replication re-priming, ensuring discontinuous progression of DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…Replisome components are usually stably associated to replication forks 27 . Tipin is required for efficient Pol α binding to chromatin, and it has been shown to increase processivity of all major DNA polymerases 3 , 8 . It is possible that the Tipin facilitates polymerase-mediated DNA replication re-priming, ensuring discontinuous progression of DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…Several kinases have been reported to phosphorylate CLASPIN and promote CHK1 activation, including CHK1 itself (4)(5)(6)14), casein kinase 1 gamma 1 (CK1g1; ref. 15), and CDC7 (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, cellular surveillance mechanisms that overlap with the DNA damage response pathways detect, stabilize, and resolve stalled replication forks to help preserve genome stability (2). CLASPIN, critical for both DNA synthesis and for signaling the presence of replication stress, is a ring-shaped protein that, together with the TIPIN-TIM1 complex, physically links DNA polymerases and DNA helicase (4)(5)(6); this is important for stabilization of replication forks, both during normal replication and upon prolonged arrest (1,2,7). CLASPIN also plays an important role in the replication stress response pathway (3,8,9), as ATR activation of CHK1 is favored by the binding of CHK1 to CLASPIN (2,(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…This is very slow, considering that estimates suggest that entire Okazaki fragments are synthesized and processed in under 1 s (57, 58). The loading of Pol ⑀ might be faster in vivo due to the activities of other proteins, such as GINS in the preloading complex/CMG helicase in yeast and TIM-Tipin in human cells (25,59,60). Recent in vitro reconstitution experiments showed that CMG helicase selects Pol ⑀ over Pol ␦ on the leading strand in yeast (61).…”
mentioning
confidence: 99%